IMPLIKASI HUKUM PENGECEKAN SERTIFIKAT SECARA ONLINE TERHADAP PPAT - Sundaru Guntur W (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
Land Deed Maker Officials are public officials and extensions of BPN authorized by the government to make authentic deeds regarding all legal actions regarding land rights and property rights to flat units. So before PPAT makes a deed of sale and purchase of land, PPAT is obliged to conduct an examination of the original certificate of the land to the Land Office before making a deed of sale and purchase of land because this is a requirement for making a deed of sale and purchase of land. The deed made by PPAT is one of the data sources for the maintenance of land registration data. This is regulated in the Regulation of the Minister of State for Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration Article 97, this regulation was made to implement PP RI No. 3 of 1997. However, not all PPATs do this. that matter. In Indonesia there are still PPATs that do not check and check the original land certificates. This is because there are several obstacles faced by PPAT in checking and this does not close the implementation of PPAT's responsibility in checking land certificates before making the deed of sale and purchase of land. Checking land certificates online is not only faster and easier, there are also risks, including system errors, certificates that turn out to be fake, certificates that turn out to be double. This risk also has the potential to become a problem, both criminal and civil, for both PPAT and BPN.